Предмет: Алгебра,
автор: Аноним
решите
Ответы
Автор ответа:
0
x³+2x²-3x=x(x²+2x-3)=x(x+3)(x-1)
x²+2x-3=0
x1+x2=-2 U x1*x2=-3⇒x1=-3 U x2=1
(x³+2x²-3x)/(x²+3x)=x(x+3)(x-1)/[x(x+3)=x-1
x²+2x-3=0
x1+x2=-2 U x1*x2=-3⇒x1=-3 U x2=1
(x³+2x²-3x)/(x²+3x)=x(x+3)(x-1)/[x(x+3)=x-1
Автор ответа:
0
а можно подробнее
Похожие вопросы
Предмет: Алгебра,
автор: sashagaar
Предмет: Қазақ тiлi,
автор: mako6578
Предмет: Биология,
автор: pecenukigor882
Предмет: Геометрия,
автор: arkaeva1
Предмет: Алгебра,
автор: yfnfkbzvehflbtdyf